2019
DOI: 10.1088/1361-6595/ab30ec
|View full text |Cite
|
Sign up to set email alerts
|

Emission and absorption diagnostics of a diffuse dielectric barrier discharge with multiple current peaks in helium at atmospheric pressure

Abstract: Dielectric barrier discharge (DBD) is a simple means to sustain low-temperature diffuse discharges at atmospheric pressure. As atmospheric pressure plasma processing requires DBDs to work under various operating conditions, even diffuse discharges are often observed to exhibit multiple current peaks. In this work, multiple current peaks helium DBD is obtained by adding small concentration of argon in a nominally pure helium discharge. As the concentration of argon increases, multiple current peaks emerge while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
4
1
0
Order By: Relevance
“…For comparable voltage amplitudes, the measured current curve exhibits two distinguishable regions: (a) the sinusoidal portion, which is associated with the displacement current, and (b) the broad peaks, which are linked to the discharge current in a homogeneous or glow‐like multipeak discharge regime. [ 21,28 ] However, the number of peaks increases for partially outgassed samples; a similar feature was observed by Levasseur et al [ 21 ] in a N 2 /HMDSO DBD in the presence of partially outgassed wood.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…For comparable voltage amplitudes, the measured current curve exhibits two distinguishable regions: (a) the sinusoidal portion, which is associated with the displacement current, and (b) the broad peaks, which are linked to the discharge current in a homogeneous or glow‐like multipeak discharge regime. [ 21,28 ] However, the number of peaks increases for partially outgassed samples; a similar feature was observed by Levasseur et al [ 21 ] in a N 2 /HMDSO DBD in the presence of partially outgassed wood.…”
Section: Methodssupporting
confidence: 73%
“…The multilayer substrate is shown as four differently colored layers for the sake of clarity a homogeneous or glow-like multipeak discharge regime. [21,28] However, the number of peaks increases for partially outgassed samples; a similar feature was observed by Levasseur et al [21] in a N 2 /HMDSO DBD in the presence of partially outgassed wood.…”
Section: Plasma Deposition Of Organosilicon Coatingssupporting
confidence: 75%
“…In addition, the slight bump after the main current peak is more pronounced in presence of outgassing impurities than in outgassed conditions. This is consistent with the results reported in the literature for nominally high-purity He DBD in presence of Ar admixtures [44]. Similar variations are observed in charge measurements.…”
Section: Influence Of Substrate Outgassingsupporting
confidence: 93%
“…This point must, however, be verified by fast imaging (see additional details below). It must be noted that the small bump can originates from a second breakdown occurring after the first discharge because of the continuous increase of the gas voltage up to values higher than the breakdown voltage [44,45]. Under such conditions, the discharge power rises from 4.1 W at 2 min to 5.1 W at 60 min.…”
Section: Influence Of the Frequency Of The Applied Voltagementioning
confidence: 99%
“…The observed delay in H β line emission at higher working gas flows is very similar to the results obtained in experiments in DBDs [31,34] and in the afterglow of pulsed discharges [82,83], where is shown that the helium metastable atoms and molecules play a very important role in the excitation of hydrogen atoms in different kind of discharges. Also, the evolution of the H β line intensity for different gas flow rates, see figure 8, is very similar to the evolution of helium atom metastable density, measured for different gas flow rates [75] and different concentration of impurities [75,84]. It is shown in references [45,47,59,68,85,86] that the density of the helium metastables increases with increasing gas flow because the concentration of their quenchers (impurities) decreases.…”
Section: Spectroscopic Measurementssupporting
confidence: 74%